A study to assess perceived stress, life events and prevalence of dissociative experiences in patients with anxiety disorders - Samanta, Soumen; Nandi, Salmali; Saha, Indranil; Roy, Surjya; Bandyopadhyay, Gautam (International Journal of Research in Medical Sciences, 2024)
Background: Anxiety disorders are characterized by a central theme of intense subjective distress and apprehension of impending danger. Dissociation has been frequently associated in such patients, where it acts as a defense mechanism that allows temporary relief. Previous studies have also shown that more number of life events and higher perceived stress are seen in patients of anxiety disorder, which may even act as predictors of developing the disease. Addressing these factors may contribute to improved understanding of underlying psychopathology and better treatment outcomes. Methods: This was a cross-sectional, 1 year time bound study. As per calculation from prevalence, 161 participants were selected as sample population with specific inclusion and exclusion criteria. Socio-demographic data was collected, appropriate scales were administered to assess the required parameters and statistical analysis was carried out thereafter. Results: We found that 21.74% patients had dissociative experience, 40.37% patients had perceived stress during last month, 53.4% had less/moderate stress and 39.1% patients had severe stress. Most frequently occurring life event was financial loss or problem. Statistically significant association was found between total life events score and socio-demographic variables. Mean dissociative experience scale score was positively correlated with total perceived stress scale score and total life event score. Total perceived stress scale score was also positively correlated with total life event score. Conclusions: Anxiety disorder patients had high levels of dissociation, perceived stress and life events, and these three parameters were also correlated with each other.